Penguraian Urgensi Frasa Agama dalam Peta Jalan Pendidikan Nasional (PJPN) 2020-2035 - Roisul Ma'ruf; Reni Sasmita; Fuji Awaliah; Khusna Haibati Lathif; Alicia Anderson (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
The disappearance of religious phrases in the temporary draft of 2020-2035 National Education Roadmap (PJPN) caused various reactions including religious leaders, mass organizations, politicians, society and culturalists. It is because the draft of 2020-2035 National Education Roadmap (PJPN) contradicts with the 1945 Constitution, the National Education System Law, Government Regulations and Pancasila. This study aims to analyze the important meaning of religious phrases in the temporary draft of the 2020-2035 National Education Roadmap (PJPN). The current Educational Roadmap is designed to create religious, pious and moral students. The research method used in this study is a literature study. The results shows that religion has important position as a source of value and part of national education. Religious education plays an important role in developing students potential to have religious spirituality, noble character, and good personality. The position of religion in national education is very important in establishing human character and morals.